Evaluasi Kebijakan Pemberian Bantuan Dana Hibah Kepada Organisasi Keagamaan Pada Bagian Kesejahteraan Rakyat Sekretariat Daerah Kabupaten Nias Selatan - Duha, Pelayaran; Siagian, Nalom; Silaban, Adanan; Hondo, Wantri (Institut Agama Kristen Negeri Tarutung, 2025)
This study aims to evaluate the grant policy provided to religious organizations in South Nias Regency. Using a qualitative approach and descriptive method, data were collected through interviews, observations, and document analysis. The findings indicate that the policy has had a positive impact on social and religious programs; however, several weaknesses were identified, such as a lack of transparency, accountability, political interference, regional disparities, and limited oversight. The researcher recommends strengthening regulations, implementing objective selection processes, ensuring fair distribution, and developing participatory monitoring mechanisms to enhance the effectiveness and benefits of the policy for the community.